Intraspinal Stem Cell Transplantation in Amyotrophic Lateral Sclerosis: A Phase I Trial, Cervical Microinjection, and Final Surgical Safety Outcomes. Issue 1 (5th September 2013) - Riley, Jonathan; Glass, Jonathan; Feldman, Eva L.; Polak, Meraida; Bordeau, Jane; Federici, Thais; Johe, Karl; Boulis, Nicholas M.
Abstract: BACKGROUND: The first US Food and Drug Administration approved clinical trial for a stem cell-based treatment of amyotrophic lateral sclerosis has now been completed. OBJECTIVE: Primary aims assessed the safety of a direct microinjection-based technique and the toxicity of neural stem cell transplantation to the ventral horn of the cervical and thoracolumbar spinal cord. Results from thoracolumbar-only microinjection groups have been previously published. Cervical and cervical plus thoracolumbar microinjection group perioperative morbidity results are presented. METHODS: Eighteen microinjection procedures (n = 12 thoracolumbar [T10/11], n = 6 cervical [C3-5]) delivered NSI-566RSC (Neuralstem, Inc), a human neural stem cell, to 15 patients in 5 cohorts. Each injection series comprised 5 injections of 10 μL at 4-mm intervals. The patients in group A (n = 6) were nonambulatory and received unilateral (n = 3) or bilateral (n = 3) thoracolumbar microinjections. The patients in groups B to E were ambulatory and received either unilateral (group B, n = 3) or bilateral (group C, n = 3) thoracolumbar microinjection. Group D and E patients received unilateral cervical (group D, n = 3) or cervical plus bilateral thoracolumbar microinjection (group E, n = 3). RESULTS: Unilateral cervical (group D, n = 3) and cervical plus thoracolumbar (group E, n = 3) microinjections to the ventral horn have been completed in ambulatory patients. One patient developed a postoperative kyphotic deformity prompting completion of a laminoplasty in subsequent patients. Another required reoperation for wound dehiscence and infection. The solitary patient with bulbar amyotrophic lateral sclerosis required perioperative reintubation. CONCLUSION: Delivery of a cellular payload to the cervical or thoracolumbar spinal cord was well tolerated by the spinal cord in this vulnerable population. This encouraging finding supports consideration of this delivery approach for neurodegenerative, oncologic, and traumatic spinal cord afflictions.